THE METAMORPHOSIS OF SOUTH AFRICA’S PUBLIC ORDER POLICE - Nortje, Sharon M (PINS-Psychology in Society, 2025)
Marks, M (2005) Transforming the Robocops: Changing police in South Africa. Pietermaritzburg: University of KwaZulu-Natal Press. ISBN: 1-86914-043-5. xvi + 291 Pages